The Role of Diets in Prevention and Hypertension Therapy - Felicio Araya (GoAcademica Research & Publishing, 2020)
Hypertension is one of the public health problems in the world in the last decade. Various studies show hypertension is a major risk factor in the occurrence of stroke, ischemic heart disease, and kidney failure. Hypertension therapy can reduce the risk of stroke by 40% and myocardial infarction risk by up to 15%. Lifestyle changes that are part of the management of hypertension can reduce blood pressure, increase the effectiveness of antihypertensive drugs, and reduce cardiovascular risk. Modification of daily food intake patterns is one component of lifestyle changes that have the greatest role in lowering blood pressure. Modification of food intake patterns referred to is to follow the general guidelines for balanced nutrition also in accordance with the dietary approach to stop hypertension (DASH), which is high in vegetables and fruit, high-fiber foods, low-fat milk, meat, and nuts. It should also be noted that energy intake, the amount and type of protein, and fat and carbohydrate components. In addition, foodstuffs are rich in minerals and vitamins, and specific nutrients, such as omega-3 unsaturated fatty acids have a role in the prevention and management of hypertension.